Possibilities of three phase scintigraphy in the diagnosis of diabetic osteoarthropathy - M. A. Zorkaltsev; V. D. Zavadovskaya; O. Yu. Kilina; A. P. Kurazhov; O. S. Shoulga; V. D. Udodov; Ye. A. Krasilnikova; A. A. Ulbrekht; K. M. Popov (Бюллетень сибирской медицины, 2012)
Establishing informative of 3-phase scintigraphy in the evaluation of blood flow and identify pyo-inflammatory process in patients with neuropathic, ischemic, and mixed forms of diabetic foot. This study includes the results of three-phase scintigraphy of 76 patients with diabetes mellitus and with suspicion of osteomyelitis in diabetic foot. Results were verified with morphological study in 39 patient.In patients with diabetic foot the depression of the main vessels blood flow and blood flow prevalence the changes intraosseous blood flow. Comparison of scintigraphy and morphological studies confirmed the highly informative three-phase scintigraphy in the evaluation of main and peripheral blood flow. 3-phase scintigraphy revealed a lower specificity (66.7%) in the diagnosis of osteomyelitis in patients with diabetes mellitus at the sensitivity (94.7%) and accuracy (73.7%).Three-phase scintigraphy is high-performance method in revealing the arterial and peripheral blood flow disorder in patients with diabetes mellitus. The low specificity of the three-phase scintigraphy with high sensitivity indicate the limited possibilities of the method in the identification of pyo-inflammatory process in patients with diabetes mellitus. The observed preservation of blood flow makes it possible to expand the employment of methods of nuclear medicines and apply scintigraphy with labeled leukocytes for indicating purulent infection in patients with complicated course.